Natural convection and radiation in rectangular cavities with one active vertical wall - Karatas, Hakan; Derbentli, Taner (Elsevier BV, 2018)
Abstract Natural convection and radiation in rectangular cavities with aspect ratios of 1, 2.09, 3, 4, 5 and 6 has been studied. All six cavities have a height of 340 mm and a depth of 210 mm. The cavities have different lengths. The cavity is closed, filled with air, and has one active vertical wall. The opposing vertical wall is inactive. The other four walls are adiabatic. Experiments are performed to study the heat transfer in the cavity. Thermocouples are used to measure the temperature. In each cavity case, the temperature distribution between the vertical walls of the cavity is obtained at 35 positions in the length, seven positions in the height and one position in the depth directions. Temperature field is presented at the mid-depth of the cavity. In the central region of the cavity, the temperature is nearly constant, and the fluid is almost stagnant. Heat transfer correlation is obtained for the Rayleigh number range of 1.60 × 105 to 4.67 × 107, and the aspect ratio range of 1 to 6. The variations of the temperature profile and the local Nusselt number along the cavity height are presented.